Case Report: Acute Retinal Necrosis after Intravitreal Ranibizumab for Exudative Macular Degeneration. Issue 3 (March 2021) - Pan, Ying; Huang, Xiaoli; Wu, Zhifeng; Lu, Shui; Chen, Tiantian; Zou, Wenjun
ABSTRACT: SIGNIFICANCE: Acute retinal necrosis (ARN) may occur after intravitreal ranibizumab (IVR) treatment for patients with exudative age-related macular degeneration (AMD). Awareness of this unusual but devastating complication after IVR is needed. Early identification may help provide timely antiviral treatment and prevent irreversible visual loss. PURPOSE: This study aimed to report a case of ARN after IVR in a patient with exudative AMD. CASE REPORT: A 67-year-old male patient complained of blurred vision in his left eye for 1 month. The patient was diagnosed with exudative AMD after detailed ophthalmic clinical evaluations. He received IVR once in his left eye. Three days after IVR, he developed varicella-zoster virus–associated ARN, which was treated with systemic and intravitreal antiviral therapy. Because of progressive inflammation, the patient underwent 25G pars plana vitrectomy with silicone oil tamponade. Seven months later, the patient was administered intravitreal aflibercept once in his left eye. Three months after intravitreal aflibercept, he underwent removal of silicone oil, and retinal detachment occurred 2 weeks after the surgery because of low IOP, and the patient eventually discontinued treatment. CONCLUSIONS: This study reports the first case of varicella-zoster virus–associated ARN after IVR. Early ARN may be very difficult to distinguish from intraocular inflammation after IVR. Therefore, early detection of viral DNA in the intraocular fluid using polymerase chain reaction is recommended. Immediate antiviral treatment may be beneficial to prevent severe visual loss.